Efficacy and Safety of Rozanolixizumab in Moderate to Severe Generalized Myasthenia Gravis: A Phase 2 Randomized Control Trial. (9th February 2021) - Bril, Vera; Benatar, Michael; Andersen, Henning; Vissing, John; Brock, Melissa; Greve, Bernhard; Kiessling, Peter; Woltering, Franz; Griffin, Laura; Van den Bergh, Peter; ,
Abstract : Objective: To explore the clinical efficacy and safety of subcutaneous (SC) rozanolixizumab, an anti-neonatal Fc receptor humanized monoclonal antibody, in patients with generalized myasthenia gravis (gMG). Methods: In this phase 2a, randomized, double-blind, placebo-controlled, 2-period, multicenter trial (NCT03052751), patients were randomized (1:1) in period 1 (days 1–29) to 3 once-weekly (Q1W) SC infusions of rozanolixizumab 7 mg/kg or placebo. In period 2 (days 29–43), patients were re-randomized to either rozanolixizumab 7 mg/kg or 4 mg/kg (3 Q1W SC infusions), followed by an observation period (days 44–99). Primary endpoint was change from baseline to day 29 in Quantitative Myasthenia Gravis (QMG) score. Secondary endpoints were change from baseline to day 29 in MG–Activities of Daily Living (MG-ADL) and MG-Composite (MGC) scores and safety. Results: Forty-three patients were randomized (rozanolixizumab 21, placebo 22 [period 1]). Least squares (LS) mean change from baseline to day 29 for rozanolixizumab vs placebo was as follows: QMG (LS mean −1.8 vs −1.2, difference −0.7, 95% upper confidence limit [UCL] 0.8; p = 0.221; not statistically significant), MG-ADL (LS mean −1.8 vs −0.4, difference −1.4, 95% UCL −0.4), and MGC (LS mean −3.1 vs −1.2, difference −1.8, 95% UCL 0.4) scores. Efficacy measures continued to improve with rozanolixizumab 7 mg/kg in period 2. The most common adverse event in period 1 was headache (rozanolixizumab 57%, placebo 14%). Conclusion: Whereas change from baseline in QMG was not statistically significant, the data overall suggest rozanolixizumab may provide clinical benefit in patients with gMG and was generally well tolerated. Phase 3 evaluation is ongoing (NCT03971422). Classification of Evidence: This study provides Class I evidence that for patients with gMG, rozanolixizumab is well-tolerated, but did not significantly improve QMG score.